The Essence of Internal Audit and Its Objectives - Klaudia Skelnik; Bożenna Piątkowska (Communications of International Proceedings, 2022)
Purpose: The aim of the article is to discuss the essence and objectives of internal audit. The origin and the notion of internal audit are also discussed, based on foreign and Polish literature. There are also considerations related to tasks and functions of audit, including the procedures of carrying out internal audits at an organisation. In the article, the important role of internal audit in an organisation is emphasized, considering its objective and supportive character, which provides added value and contributes to the improvement of the organisation. Design/Methodology/Approach: During the research, the analysis of literature was applied, with the use of the critical, descriptive and explanatory methods. Findings: In the article, growing significance of internal audit is indicated, particularly in the field of improving management in modern organisations. It is more and more often possible to observe that internal audit comes as a method applied to streamline operations of an organisation. Practical Implications: The content compiled and presented in the article can be useful in considerations on the objectives of internal audit in an organisation and various benefits it can bring to that organisation. Furthermore, it can also allow the management of the organisation to realize that internal audit comes as a tool offering great opportunities. Originality/Value: enhancement of knowledge on internal audit, with the use of various literary sources; indication of its important role in an organisation. The specificity of internal audit is indicated with the consideration of the following facts: audit is applied to analyse compliance, it has got aims and features that are strictly and precisely defined and it is a process that is performed to achieve particular tasks.
Keywords: internal audit; history of internal audit; risk analysis; a process; methods of internal audit; standards of internal audit.